Immigration status and its relationship with delinquency, drug use, and gang membership in the English-speaking Caribbean - Freemon, Kayla (Journal of ethnicity in criminal justice, 2025)
Research demonstrates that the foreign-born population engages in less offending than their native-born counterparts. Much of the literature, however, originates in the United States and Europe. The current study examines the individual-level immigration-delinquency link among 11,485 youth in seven English-speaking Caribbean nations using bivariate comparisons and multivariate regression analyses by nation focused on six measures of delinquency. With few exceptions, migrants were not significantly more likely to engage in violence, gang membership, or drug sales. However, we observed mixed results regarding the relationship between immigration status and property offending, and alcohol and marijuana use across several nations, with immigration status serving as a risk factor in some countries and a protective factor in others.